From Policy to Pedagogy: English Teachers’ Lesson Planning and Classroom Enactment of Mindful, Meaningful, and Joyful Learning - Romzi, Muhamad Romzi; Junaidi , M.; Yusri, Ahmad; Fikni, Zahratul (LITPAM, 2026)
This study investigates the implementation of Mindful, Meaningful, and Joyful Learning (MMJL) principles within the Merdeka Curriculum framework in English language teaching at SDN 01 Pijot Utara. The research subjects consisted of a sixth-grade English teacher who served as both the designer of the Teaching Module and the classroom practitioner, along with sixth-grade students as secondary participants. Adopting a qualitative descriptive case study design grounded in Policy Enactment theory, data were collected through document analysis of the Teaching Module and systematic classroom observations. The findings reveal that while the MMJL principles are thoroughly embedded in the macro-structural design of the Teaching Module and successfully enacted during foundational and receptive instructional phases, a significant divergence occurs during productive phases. Activities demanding student autonomy, such as independent writing, reflection, and collaborative summarization, were only partially enacted, largely due to a lack of anticipatory scaffolding in the written plan and the persistence of teacher-centered norms intended to manage classroom silence. The study concludes that although MMJL principles effectively support classroom management and emotional well-being, their potential to drive higher-order intellectual engagement remains constrained by the gap between policy intentions and classroom realities. Practically, this research contributes to curriculum development and teacher training by recommending that Teaching Modules evolve into dynamic pedagogical instruments, supplemented by anticipatory scaffolds and differentiated strategies, to bridge the distance between curriculum vision and practice.